Effects of Gender and Apolipoprotein E on Novelty MMN and P3a in Healthy Elderly and Amnestic Mild Cognitive Impairment - Gao, Lijuan; Chen, Jiu; Gu, Lihua; Shu, Hao; Wang, Zan; Liu, Duan; Yan, Yanna; Zhang, Zhijun (Frontiers in Aging Neuroscience, 2018)
Background: The apolipoprotein E epsilon4 (ApoE ε4) allele and female gender may be important risk factors for the development of Alzheimer’s disease (AD) and amnestic mild cognitive impairment (aMCI). Novelty mismatch negativity (MMN) represents the pre-attentive index of deviance detection and P3a represents the attention orienting response. Furthermore, MMN and P3a components have been reported to be potential markers in aMCI. Therefore, this study will investigate the effects of gender and ApoE on auditory novelty MMN and P3a and their relationship to neuropsychological performance in aMCI. Methods: 39 aMCI subjects and 44 controls underwent neuropsychological assessment and ApoE genotyping. Novelty MMN and P3a components were investigated during an auditory novelty oddball task. Results: Firstly, novelty MMN latency was significantly shorter in aMCI than in the healthy control (HC) group. Secondly, novelty MMN latency was negatively correlated with episodic memory in aMCI, but not in HC. Novelty P3a latency was negatively correlated with information speed processing in all subjects. For gender effect, novelty MMN latency was shorter in aMCI females than in HC females. Moreover, novelty P3a amplitudes were lower in males than in females in both aMCI and HC. For the effect of ApoE status, novelty MMN latency was shorter in aMCI ApoE ε4- than HC ApoE ε4-. Conclusions: aMCI present altered pre-attentive processing indexed by novelty MMN components. Furthermore, there may be a compensatory mechanism on the impaired processing in aMCI. It further suggest that aMCI female and ApoE ε4- recruited the compensatory mechanism.